The Relationship between Leadership Styles and Employee Commitment in Public Organizations of Dire Dawa Administration, Ethiopia - Aschalew Mulugeta , Dr. A.V.R Pandian (International Journal of Advanced Science and Technology, 2020)
The primary objective of this study is to analyze the relationship between different leadership styles and employee commitment in public organizations of Ethiopia with special reference to Dire Dawa Administration. For this study the researchers have applied stratified proportionate random sampling technique in which 597 sample respondents from 15 different public organizations of DDA are taken as sample size. Primary data collection method is used to collect information from the selected sample respondents comprising of leaders and employees from the administration by using Multi-factor Leadership Questionnaire (MLQ) and Organizational Commitment Questionnaire (OCQ). Descriptive statistics, two-tailed Pearson correlation analysis and independent sample T-test at 95% CL are used for data analysis. This study points out there are significant differences between the two samples on all dimensions of leadership except management by exception (active) and overall transactional leadership scale. Transformational leadership style is more effective than transactional leadership in affecting all subscales of employees’ organizational commitment. However, laissez-faire leadership has a negative correlation with employees’ affective commitment. But it does not have any significant correlation to both continuance and normative commitments. Hence, it is recommended that the leaders of DDA public organizations should focus more on developing efficient team work and express warm concern and trust to co-workers through transformational leadership behavior.